Analisis Faktor-Faktor Determinan Pada Motivasi Membayar Zakat - Desky, Harjoni (Al Mabhats : Jurnal Penelitian Sosial Agama, 2016)
This study aimed to know the factors of Worship, Zakat Knowledge, Wealth, Role of Government, The Role of Ulama and the Credibility of institutions Amil Zakat influence of Motivation Paying Zakat, To know the factors of Worship, knowledge, charity, property , the role of government, the role of Ulema and the Credibility of Institutions influential Partial Amil Zakat and Zakat Simultaneous to the magnitude of value. The method of analysis used the method of descriptive analysis and multiple linear regression analysis. The results showed that factors of worship, knowledge of charity, property or income, the role of scholars and credibility of institutions partially amil zakat has positive and significant impact on motivation to pay zakat, while the factors positively influence the role of scholars and not significant to the motivation to pay zakat. Simultaneously factors of worship, charity knowledge, wealth or income, the role of government, the role of scholars and credibility amil zakat institutions have a positive and significant impact on motivation to pay zakat.